Low-carbon high-durability concrete
By abrasive granulation of blast furnace slag and steel slag, and compounded with desulfurization gypsum, tailings, desulfurization ash, and red mud, hydration activity is stimulated and a stable mesh gel structure is formed, which solves the poor early strength and durability of low-carbon concrete. The problem of this has achieved efficient carbon emission reduction and engineering performance improvement.
Patent Information
- Application Number
- CN202411217789.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-27
AI Technical Summary
Due to the weak hydration activity of slag and steel slag and the discrete stability of existing low-carbon concrete, the early strength and poor durability, affecting the quality of the project.
Grinding the granulated blast furnace slag and steel slag, combined with desulfurization gypsum, tailings, desulfurization ash and red mud for compounding, hydration activity is stimulated, and the dynamic chemical balance of alkalinity and sulfate ions is regulated through the exciter to form a stable The mesh gel structure improves the early strength and late durability of concrete.
It significantly improves the early strength and durability of low-carbon concrete, reduces cement use and energy consumption, and reduces CO2 emissions, improving the stability and impact toughness of concrete.
Smart Images

Figure BDA0005022060260000051 
Figure BDA0005022060260000052 
Figure BDA0005022060260000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of concrete, and in particular to a low-carbon and high-durability concrete. Background Art
[0002] Concrete is mostly made of cement, which consumes a huge amount of natural resources, damages the environment, and affects the ecological balance of the earth. In particular, CO2 emissions from cement production usually account for 5-10% of carbon emissions from human activities. Therefore, the cement industry is a veritable carbon emitter. Reducing CO2 gas emissions is a very urgent task on a global scale. At the same time, cement production consumes a large amount of natural resources, such as limestone and clay.
[0003] Under the requirements of energy conservation and emission reduction policies, the cement industry has changed its production model to minimize the use of natural resources and energy consumption. With the rapid development of the metallurgical industry, steel mills discharge up to 100 million tons of industrial waste slag, steel slag, etc. each year, which not only occupies land for storage, but also is a serious source of environmental pollution. Therefore, the industry has begun to use slag and steel slag to partially replace cement raw materials such as limestone and clay to prepare low-carbon concrete, so as to achieve waste recycling, save natural resources, and protect the ecological environment. The promotion of its use can accelerate the greening process of my country's building materials industry, and has good social, environmental and economic benefits.
[0004] However, slag and steel slag have weak hydration activity, and due to their influence, the early strength of their cementitious materials is relatively low. Also, due to the large degree of dispersion of the stability of steel slag aggregate, it is easy for hardened concrete to suffer surface damage or structural damage, resulting in poor durability and strength of the concrete. In recent years, the use of steel slag aggregate as concrete aggregate has caused frequent engineering quality problems. Summary of the invention
[0005] In order to improve the durability and strength of low-carbon concrete, the present application provides a low-carbon high-durability concrete.
[0006] In the first aspect, the present application provides a low-carbon and high-durability concrete adopting the following technical solution: A low-carbon high-durability concrete comprises the following components and their weight parts: 30-35 parts of cement, 40-46 parts of cementitious materials, 180-190 parts of coarse aggregate, 150-160 parts of fine aggregate, 4-6 parts of air-entraining and water-reducing agent and 60-70 parts of water; The cementitious material comprises the following components and their contents: 50-55% granulated blast furnace slag, 5-10% steel slag, 3-5% desulfurized gypsum, 1-3% tailings, 2-4% desulfurized ash, 2-4% red mud and 3-5% reinforcing agent, and the balance is silicate cement clinker.
[0007] By adopting the above technical scheme, steel slag and granulated blast furnace slag are cement admixtures with potential hydraulic properties. After they are ground to a certain fineness and subjected to mechanical force, their hydration activity can be stimulated so that they can undergo hydration and can replace part of the cement to act as concrete cementitious materials.
[0008] At the same time, in order to compensate for the shortcomings of weak hydration activity and large degree of stability dispersion of steel slag, the above-mentioned content of desulfurized gypsum, tailings, desulfurized ash and red mud are added for compounding. The active Al2O3 and SiO2 in the red mud react with CH to promote early hydration reaction and promote early strength, thereby compensating for the shortcomings of low early strength of steel slag cementitious materials to a certain extent; at the same time, the desulfurized gypsum neutralizes the tailings and desulfurized ash for compounding, which has a good hydration activity stimulation effect, and can greatly promote the coordinated hydration of granulated blast furnace slag and steel slag to produce a large amount of needle-shaped calcium sulfonate (AFt) crystals and amorphous CSH gel to form a stable network gel. The network gel tightly wraps the crystals, further improving the stability of the composite system, thereby improving the durability and strength of the obtained concrete.
[0009] In ready-mixed concrete, industrial solid wastes such as desulfurized gypsum, tailings, desulfurized ash and red mud, and silicate cement clinker are used as high-performance mineral admixtures to directly replace part of the cement, thereby reducing the use of cement and energy consumption, and achieving a reduction in carbon emissions. At the same time, it will not affect the use of other admixtures such as coarse aggregate and fine aggregate, and will work synergistically with other admixtures to further improve the strength and durability of concrete.
[0010] Optionally, the preparation method of the cementitious material includes the following steps: placing the granulated blast furnace slag, steel slag, desulfurized gypsum, tailings, desulfurized ash, red mud, reinforcing agent and silicate cement clinker in a mixer in sequence, stirring evenly, and then adding an activator and mixing and grinding for 25-30 minutes to obtain a cementitious material.
[0011] By adopting the above technical scheme, under the action of the activator and mixing and grinding treatment, the dynamic chemical equilibrium environment of alkalinity and sulfate ions is regulated, the formation of insoluble complex salt minerals is regulated, the saturated equilibrium state of ions dissolved in granulated blast furnace slag and steel slag is destroyed, the dissociation and dissolution of aggregates and ions in the granulated blast furnace slag and steel slag are driven, and the hydration gelation strengthening reaction process is driven, thereby stimulating the hydration activity of granulated blast furnace slag and steel slag to a greater extent, so as to effectively improve the early strength and later durability of the obtained concrete.
[0012] Optionally, the activator accounts for 2-3% of the total mass of the cementitious material, and the activator includes industrial water glass, sodium hydroxide, ethylene glycol, sodium sulfate and calcium formate in a mass ratio of 1: (0.4-0.6): (0.7-0.9): (1.1-1.3).
[0013] By adopting the above technical scheme, the activator obtained by compounding industrial water glass, sodium hydroxide, ethylene glycol, sodium sulfate and calcium formate according to the above mass ratio can better regulate the dynamic chemical equilibrium environment of alkalinity and sulfate ions, and can be compounded with desulfurized gypsum, tailings, desulfurized ash and red mud to stimulate the hydration activity of granulated blast furnace slag and steel slag to a greater extent.
[0014] Optionally, the reinforcing agent comprises straw fiber and raw soil powder in a mass ratio of 1:(1.1-1.3).
[0015] By adopting the above technical solution and adding straw fiber to the gel material, the impact toughness of the concrete material can be enhanced, which plays an effective role in preventing cracks and seepage, and further improves the durability and strength of the concrete. Since the above activator adjusts the alkalinity to a high level, it is easy to cause frosting on the surface of the desulfurized gypsum, thereby affecting the mechanical strength of the cementitious material. The products of the raw soil are mainly low-alkalinity hydrated calcium silicate and hydrated calcium aluminate gel, as well as a certain amount of zeolites, which can significantly improve the alkali-eluting phenomenon to prevent the desulfurized gypsum from frosting, thereby further improving the durability and strength of the concrete.
[0016] Optionally, the raw soil powder is obtained by drying a raw soil sample at 80°C for 48-50h and then grinding it, wherein particles with a particle size of less than 5μm account for 75-80% of the raw soil powder, and particles with a particle size of 5-50μm account for 20-25% of the raw soil powder; the straw fiber is obtained by ball milling 2-3cm straw segments for 2-3h.
[0017] Optionally, the fine aggregate includes river sand and glass fiber particles in a mass ratio of 1:(0.1-0.3).
[0018] By adopting the above technical solution, the glass fiber particles have good heat resistance, a high melting point, and can maintain their original shape after being exposed to high temperatures. They have a low thermal expansion coefficient, and the addition of glass fiber particles and river sand as fine aggregate can reduce the occurrence of cracks in concrete at high temperatures to a certain extent, and improve the compressive strength of concrete, further enhancing the durability of concrete.
[0019] Optionally, the particle size of the river sand is 0.35-0.4 mm, and the particle size of the glass optical fiber particles is 0.1-0.2 mm.
[0020] Optionally, the coarse aggregate is selected from at least one of basalt crushed stone and diabase crushed stone.
[0021] Optionally, the air-entraining and water-reducing agent is selected from at least one of alkyl aromatic sulfonates, triterpenoid saponins and lignin sulfonates.
[0022] In a second aspect, the present application provides a method for preparing low-carbon and high-durability concrete, which adopts the following technical solution: A method for preparing low-carbon and high-durability concrete, comprising the following steps: First, the cementitious material is prepared, and the above-mentioned weight portions of cement, cementitious material, coarse aggregate, fine aggregate and air-entraining water-reducing agent are added in sequence for stirring. The stirring speed is 220-230 r / min, and the stirring time is 8-12 min. Water is added in 3 times during the stirring process, and the interval between each addition is 2-3 min. After the stirring is completed, a mixture is obtained, and after curing and maintenance, a low-carbon and high-durability concrete is obtained.
[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. Add the above-mentioned content of desulfurized gypsum, tailings, desulfurized ash and red mud for compounding. The active Al2O3 and SiO2 in the red mud react with CH to promote early hydration reaction and early strength, thereby compensating for the disadvantage of low early strength of steel slag cementitious materials to a certain extent. At the same time, the desulfurized gypsum neutralizes the tailings and desulfurized ash for compounding, which has a good hydration activity stimulation effect, and can greatly promote the coordinated hydration of granulated blast furnace slag and steel slag to produce a large number of needle-shaped calcium aluminate crystals and amorphous CSH gel to form a stable network gel. The network gel tightly wraps the crystals, further improving the stability of the composite system, thereby improving the durability and strength of the obtained concrete. 2. Under the action of the activator and the mixing and grinding treatment, the dynamic chemical equilibrium environment of alkalinity and sulfate ions is regulated, the formation of insoluble complex salt minerals is regulated, the saturated equilibrium state of ions dissolved in granulated blast furnace slag and steel slag is destroyed, the dissociation and dissolution of polymers and ions in granulated blast furnace slag and steel slag are driven, and the hydration gelation strengthening reaction process is driven, thereby stimulating the hydration activity of granulated blast furnace slag and steel slag to a greater extent, so as to improve the early strength and later durability of the obtained concrete; 3. Adding straw fiber to the gel material can enhance the impact toughness of concrete materials, play an effective role in preventing cracks and seepage, and further improve the durability and strength of concrete. Since the above-mentioned activator adjusts the alkalinity to a high level, it is easy to cause frosting on the surface of desulfurized gypsum, thereby affecting the mechanical strength of the cementitious material. The products of raw soil are mainly low-alkalinity hydrated calcium silicate and hydrated calcium aluminate gel, as well as a certain amount of zeolites, which can significantly improve the alkali-eluting phenomenon to prevent the frosting of desulfurized gypsum, thereby further improving the durability and strength of concrete. DETAILED DESCRIPTION
[0024] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0025] 1. Implementation Embodiment 1: A low-carbon high-durability concrete comprises the following components and their weight parts (calculated based on 100 kg as the total): 30 parts of cement, 40 parts of cementitious material, 180 parts of coarse aggregate, 150 parts of fine aggregate, 4 parts of air-entraining water-reducing agent and 60 parts of water; The cement used is silicate cement with a strength grade of 42.5; the coarse aggregate is diabase crushed stone with a particle size of 8mm; the air-entraining water-reducing agent is lignin sulfonate.
[0026] The fine aggregate includes river sand and glass fiber particles in a mass ratio of 1:0.2. The particle size of the river sand is 0.38 mm, and the particle size of the glass fiber particles is 0.15 mm.
[0027] The cementitious material includes the following components and their contents (calculated as 50 kg in total): 53% granulated blast furnace slag, 5-10% steel slag, 3-5% desulfurized gypsum, 1-3% tailings, 2-4% desulfurized ash, 2-4% red mud and 3-5% reinforcing agent, and the balance is silicate cement clinker.
[0028] The fineness of granulated blast furnace slag, steel slag and desulfurized ash is 325 mesh, the fineness of desulfurized gypsum and red mud is 400 mesh, and the fineness of tailings is 300 mesh; silicate cement clinker is purchased from Nanchang Huangteng Building Materials Co., Ltd.; The reinforcing agent includes straw fiber and raw soil powder in a mass ratio of 1:1.2; The preparation method of raw soil powder is as follows: the raw soil sample is placed in an oven at a temperature of 80°C, dried for 48 hours, and then ground to obtain raw soil powder; the particles with a particle size of less than 5 μm account for 78% of the raw soil powder, and the particles with a particle size of 5-50 μm account for 22% of the raw soil powder; Preparation method of straw fiber: cut the rice straw into 2 cm small segments and then grind them in a ball mill for 2 hours.
[0029] The preparation method of the gelling material comprises the following steps: The above-mentioned granulated blast furnace slag, steel slag, desulfurized gypsum, tailings, desulfurized ash, red mud, reinforcing agent and silicate cement clinker are sequentially placed in a mixer, stirred evenly, and then an activator is added and mixed and ground for 28 minutes to obtain a cementitious material; The activator accounts for 2.5% of the total mass of the cementitious material, and the activator includes industrial water glass, sodium hydroxide, ethylene glycol, sodium sulfate and calcium formate in a mass ratio of 1:0.5:0.8:1.2.
[0030] The method for preparing low-carbon high-durability concrete comprises the following steps: First, prepare the cementitious material. Weigh the above-mentioned weight portions of cement, cementitious material, coarse aggregate, fine aggregate and air-entraining water-reducing agent in turn and put them into a mixer for stirring. The stirring speed is 220 r / min and the stirring time is 10 min. Water is added in 3 times during the stirring process, with an interval of 3 min between each addition. After stirring, a mixture is obtained. The mixture is cast to obtain a concrete test block, which is removed from the mold after standing indoors for 24 h. The test piece is placed in a standard curing room for curing for 28 days to obtain a low-carbon and high-durability concrete sample.
[0031] Embodiment 2-3: A low-carbon high-durability concrete, the differences from Example 1 are shown in Table 1.
[0032] Table 1: Embodiment 4-5: A low-carbon high-durability concrete, the differences from Example 2 are shown in Table 2.
[0033] Table 2: Embodiment 6: A low-carbon high-durability concrete, which is different from Example 2 in that the activator accounts for 2% of the total mass of the cementitious material.
[0034] Embodiment 7: A low-carbon high-durability concrete, which is different from Example 2 in that the activator accounts for 3% of the total mass of the cementitious material.
[0035] Embodiment 8: A low-carbon high-durability concrete, which is different from Example 2 in that the mass ratio of industrial water glass, sodium hydroxide, ethylene glycol, sodium sulfate and calcium formate in the activator is 1:0.4:0.7:1.1.
[0036] Embodiment 9: A low-carbon high-durability concrete, which is different from Example 2 in that the mass ratio of industrial water glass, sodium hydroxide, ethylene glycol, sodium sulfate and calcium formate in the activator is 1:0.6:0.9:1.3.
[0037] Embodiment 10: A low-carbon high-durability concrete, which is different from Example 2 in that the mass ratio of straw fiber to raw soil powder in the reinforcing agent is 1:1.1.
[0038] Embodiment 11: A low-carbon high-durability concrete, which is different from Example 2 in that the mass ratio of straw fiber to raw soil powder in the reinforcing agent is 1:1.2.
[0039] Embodiment 12: A low-carbon high-durability concrete, which is different from Example 2 in that: the particles with a particle size of less than 5 μm in the raw soil powder account for 75%, and the particles with a particle size of 5-50 μm in the raw soil powder account for 25%.
[0040] Embodiment 13: A low-carbon high-durability concrete, which is different from Example 2 in that: 80% of the raw soil powder has particles with a particle size of less than 5 μm, and 20% of the raw soil powder has particles with a particle size of 5-50 μm.
[0041] Embodiment 14: A low-carbon high-durability concrete, which is different from Example 2 in that the fine aggregate includes river sand and glass optical fiber particles in a mass ratio of 1:0.1.
[0042] Embodiment 15: A low-carbon high-durability concrete, which is different from Example 2 in that the fine aggregate includes river sand and glass optical fiber particles in a mass ratio of 1:0.3.
[0043] Embodiment 16: A low-carbon and high-durability concrete, which is different from Example 2 in that the particle size of the river sand is 0.35 mm, and the particle size of the glass optical fiber particles is 0.1 mm.
[0044] Embodiment 17: A low-carbon high-durability concrete, which is different from Example 2 in that the particle size of the river sand is 0.4 mm, and the particle size of the glass optical fiber particles is 0.2 mm.
[0045] Embodiment 18: A low-carbon high-durability concrete, which is different from Example 2 in that the coarse aggregate is basalt crushed stone.
[0046] Embodiment 19: A low-carbon high-durability concrete, which is different from Example 2 in that the air-entraining water-reducing agent is an alkyl aromatic sulfonate.
[0047] Embodiment 20: A low-carbon high-durability concrete, which is different from Example 2 in that the air-entraining and water-reducing agent is triterpene saponin.
[0048] 2. Comparison Comparative Example 1: The difference from Example 2 is that an equal amount of desulfurized gypsum is replaced by silicate cement clinker.
[0049] Comparative Example 2: The difference from Example 2 is that the tailings are replaced by silicate cement clinker in equal amount.
[0050] Comparative Example 3: The difference from Example 2 is that an equal amount of desulfurized ash is replaced by silicate cement clinker.
[0051] Comparative Example 4: The difference from Example 2 is that an equal amount of red mud is replaced by silicate cement clinker.
[0052] Comparative Example 5: The difference from Example 2 is that an equal amount of straw fibers is replaced by raw soil powder.
[0053] Comparative Example 6: The difference from Example 2 is that the glass optical fiber particles are replaced with river sand in equal amounts.
[0054] 3. Performance test A control group was set up: the cementitious material in the present application was replaced with an equal weight portion of silicate cement with a strength grade of 42.5, and concrete specimens of the control group were obtained according to the preparation method of the present application.
[0055] 1) Compressive strength test: According to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the compressive strength of the concrete specimens prepared in Examples 1-20, Comparative Examples 1-6 and the control group at the curing age of 7d and 28d was tested respectively, with 3 specimens in each group, and the results were averaged. The test results are shown in Table 3.
[0056] 2) Setting time test: According to GB / T 1346-2011 “Test Method for Water Consumption, Setting Time and Stability of Cement Standard Consistency”, the initial setting and final setting times of the concrete specimens prepared in Examples 1-20, Comparative Examples 1-6 and the control group were tested, and the test results are shown in Table 3.
[0057] 3) Compressive strength test after aging: The concrete specimens prepared in Examples 1-20, Comparative Examples 1-6 and the control group were placed in a UV aging box with an ultraviolet intensity of 210 W / m 2, the aging temperature is 60°C, and the aging time is 10 days; the compressive strength of the aged concrete specimens is tested according to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", and the test results are shown in Table 3.
[0058] Table 3: 4. Results Analysis and Summary Combining Examples 1-3 and Table 3, it can be seen that the weight portions of the components contained in the concrete of Examples 1-3 are all different. It can be seen from Table 3 that the setting time, 7d, 28d compressive strength and compressive strength after aging of the concrete specimens prepared in Examples 1-3 are all comparable to those of the control group, and the setting time, 7d, 28d compressive strength and compressive strength after aging of the concrete specimens of Example 2 are all better than those of Examples 1 and 3.
[0059] From the above, it can be seen that the early strength and durability of the concrete prepared by compounding the components according to the weight range of this application are equivalent to those of ordinary cement concrete; and the early strength and durability of the concrete prepared according to the weight range of Example 2 are relatively better.
[0060] Combining Example 2, Examples 4-5 and Table 3, it can be seen that the contents of the various components of the cementitious materials of Examples 4-5 are different. It can be seen from Table 3 that the setting time, 7d, 28d compressive strength and compressive strength after aging of the concrete specimens of Examples 4-5 are comparable to those of the control group, but the setting time, 7d, 28d compressive strength and compressive strength after aging of the concrete specimens of Example 2 are better than those of Examples 4-5.
[0061] In combination with Example 2, Comparative Examples 1-4 and Table 3, it can be seen that in Comparative Example 1, an equal amount of desulfurized gypsum is replaced with silicate cement clinker, in Comparative Example 2, an equal amount of tailings is replaced with silicate cement clinker, in Comparative Example 3, an equal amount of desulfurized ash is replaced with silicate cement clinker, and in Comparative Example 4, an equal amount of red mud is replaced with silicate cement clinker. As can be seen from Table 3, the setting time, 7d, 28d compressive strength and compressive strength after aging of the concrete specimens of Comparative Examples 1-4 are much lower than those of Example 2 and the control group.
[0062] It can be concluded that compounding granulated blast furnace slag, steel slag, desulfurized gypsum, tailings, desulfurized ash and red mud can significantly improve the early strength and durability of low-carbon concrete.
[0063] Combining Example 2, Example 8-9 and Table 3, it can be seen that the mass ratios of industrial water glass, sodium hydroxide, ethylene glycol, sodium sulfate and calcium formate in the activator of Example 8-9 are different from those in Example 2. As can be seen from Table 3, the setting time, 7d, 28d compressive strength and compressive strength after aging of the concrete specimens of Example 8-9 are all comparable to those of the control group. It can be seen from the above that the early strength and durability of the concrete prepared by compounding industrial water glass, sodium hydroxide, ethylene glycol, sodium sulfate and calcium formate as an activator according to the mass ratio range of this application are comparable to those of ordinary cement concrete.
[0064] Combining Example 2, Examples 10-11 and Table 3, it can be seen that the mass ratio of straw fiber and raw soil powder in the reinforcing agent of Example 10-11 is different from that of Example 2. As can be seen from Table 3, the setting time, 7d, 28d compressive strength and compressive strength after aging of Examples 10-11 are comparable to those of the control group. And combined with Comparative Example 5, Comparative Example 5 replaces the straw fiber with raw soil powder in equal amounts. As can be seen from Table 3, the setting time, 7d, 28d compressive strength and compressive strength after aging of the concrete specimens of Comparative Example 5 are much lower than those of Example 2 and the control group. From the above, it can be obtained that compounding straw fiber and raw soil powder as a reinforcing agent can significantly improve the early strength and durability of low-carbon concrete.
[0065] Combining Example 2, Examples 14-15 and Table 3, it can be seen that the mass ratio of river sand and glass optical fiber particles in the fine aggregate of Examples 14-15 is different from that of Example 2. As shown in Table 3, the setting time, 7d, 28d compressive strength and compressive strength after aging of Examples 14-15 are comparable to those of the control group.
[0066] In addition, in Comparative Example 6, the glass fiber particles are replaced with river sand in equal amounts. From Table 3, it can be seen that the setting time, 7d and 28d compressive strength and compressive strength after aging of the concrete specimens of Comparative Example 6 are much lower than those of Example 2 and the control group. From the above, it can be concluded that compounding river sand and glass fiber particles as fine aggregate can significantly improve the early strength and durability of low-carbon concrete.
[0067] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, all equivalent changes made according to the products, methods, and principles of the present application should be included in the protection scope of the present application.
Claims
1. A low-carbon high-durability concrete, characterized in that: It includes the following components and their weight parts: 30-35 parts of cement, 40-46 parts of cementitious materials, 180-190 parts of coarse aggregate, 150-160 parts of fine aggregate, 4-6 parts of air-entraining and water-reducing agent and 60-70 parts of water; The cementitious material comprises the following components and their contents: 50-55% granulated blast furnace slag, 5-10% steel slag, 3-5% desulfurized gypsum, 1-3% tailings, 2-4% desulfurized ash, 2-4% red mud and 3-5% reinforcing agent, and the balance is silicate cement clinker.
2. The low-carbon high-durability concrete according to claim 1, characterized in that: The preparation method of the cementitious material comprises the following steps: placing the granulated blast furnace slag, steel slag, desulfurized gypsum, tailings, desulfurized ash, red mud, reinforcing agent and silicate cement clinker in a mixer in sequence, stirring evenly, and then adding an activator for mixing and grinding for 25-30 minutes to obtain the cementitious material.
3. The low-carbon high-durability concrete according to claim 1, characterized in that: The activator accounts for 2-3% of the total mass of the cementitious material, and the activator includes industrial water glass, sodium hydroxide, ethylene glycol, sodium sulfate and calcium formate in a mass ratio of 1: (0.4-0.6): (0.7-0.9): (1.1-1.3).
4. The low-carbon high-durability concrete according to claim 1, characterized in that: The reinforcing agent comprises straw fiber and raw soil powder in a mass ratio of 1:(1.1-1.3).
5. The low-carbon high-durability concrete according to claim 4, characterized in that: The raw soil powder is obtained by drying a raw soil sample at 80°C for 48-50 hours and then grinding it. In the raw soil powder, particles with a particle size of less than 5μm account for 75-80%, and particles with a particle size of 5-50μm account for 20-25%; the straw fiber is obtained by ball milling 2-3h from 2-3cm rice straw segments.
6. The low-carbon high-durability concrete according to claim 1, characterized in that: The fine aggregate includes river sand and glass optical fiber particles in a mass ratio of 1:(0.1-0.3).
7. The low-carbon high-durability concrete according to claim 6, characterized in that: The particle size of the river sand is 0.35-0.4 mm, and the particle size of the glass optical fiber particles is 0.1-0.2 mm.
8. The low-carbon high-durability concrete according to claim 1, characterized in that: The coarse aggregate is selected from at least one of basalt crushed stone and diabase crushed stone.
9. The low-carbon high-durability concrete according to claim 1, characterized in that: The air-entraining water-reducing agent is selected from at least one of alkyl aromatic sulfonates, triterpenoid saponins and lignin sulfonates.
10. A method for preparing low-carbon high-durability concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: First, the cementitious material is prepared, and the above-mentioned weight portions of cement, cementitious material, coarse aggregate, fine aggregate and air-entraining water-reducing agent are added in sequence for stirring. The stirring speed is 220-230 r / min, and the stirring time is 8-12 min. Water is added in 3 times during the stirring process, and the interval between each addition is 2-3 min. After the stirring is completed, a mixture is obtained, and after curing and maintenance, a low-carbon and high-durability concrete is obtained.
Citation Information
Cited By
Low-clinker cement-based concrete, decorative concrete member and application
CN119797849A
Low-carbon gel material for concrete road as well as preparation method and application of low-carbon gel material
CN120208562A
A low-carbon gel material for concrete roads and a preparation method and application thereof
CN120208562B
Preparation method and texture process of high-strength concrete material
CN121627373A
